A colorimetric immuno-microarray for the quantitation and direct visualization of illicit drugs in body fluids. Issue 2 (9th November 2020) - Zhang, Lingling; Li, Xiaochun; Li, Yunchao; Yu, Hua-Zhong
Abstract : The design and testing of integrated colorimetric microarray immunochips (immuno-microarrays) are reported for the quantitation and direct visual determination of multiple illicit drugs ( e.g., morphine, cocaine and amphetamine) in body fluids. Abstract : The design and testing of integrated colorimetric microarray immunochips (immuno-microarrays) are reported for the quantitation and direct visual determination of multiple illicit drugs ( e.g., morphine, cocaine and amphetamine) in body fluids. Such an immuno-microarray platform utilizes a competitive immunoassay format, which is based on silver staining for quantitative detection and multicolor staining for direct visualization ( i.e., qualitative identification) of analytes present in the sample. Under optimized conditions, the dynamic response ranges of 3.7–1000, 1.1–300 and 1.5–300 ng mL −1 were achieved for amphetamine, cocaine, and morphine, respectively, which are wider towards low concentrations than those of standard enzyme-linked immunosorbent assay (ELISA) tests. The limits of detection (LODs) for morphine, cocaine, and amphetamine were determined to be 1.5 ± 0.1, 1.1 ± 0.1 and 3.7 ± 0.2 ng mL −1, respectively in oral fluids, which meet government regulations for law enforcement. The obvious advantages of multiplexing, simultaneous visual recognition, and accurate quantitation make the on-site detection feasible, confirming that such a colorimetric immuno-microarray holds promise for practical applications.